SCIENTIFIC AND THEORETICAL FOUNDATIONS OF DEVELOPING SPEECH IN PRIMARY SCHOOL STUDENTS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This scientific article examines the development of speech in primary school students from a scientific and theoretical perspective. The psychological and pedagogical foundations of speech development, the internal relationship between language and cognition, as well as didactic methods for developing speech activity during the primary education period are highlighted. The article also reveals the scientific principles underlying modern approaches and technologies aimed at improving students’ oral and written communication skills. The research results contribute to increasing the effectiveness of speech development practices in primary school education.